Pemanfaatan Fly Ash sebagai Bahan Subtitusi Parsial Semen pada Beton Memadat Sendiri: The Utilization of Fly Ash as Partial Substitution of Cement to the Self Compacting Concrete - NGUDIYONO NGUDIYONO; NI NYOMAN KENCANAWATI; RIZKY PRAKARSA (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2022)
ABSTRACT Self Compaction Concrete (SCC) is concrete that can flow and fill the spaces in the mold without a compaction process in a fresh state. Therefore, it can overcome various problems during the casting of building components, such as reducing construction time and the number of labor for compaction and vibration. It also can reduce noise, increase the density of concrete structural elements in parts that are difficult to reach with a compactor, and increase the quality and strength of concrete structures. The cement production process increases carbon dioxide (CO2) gas emissions. It is necessary to find alternative materials to reduce these negative impacts, namely by utilizing coal-burning waste in the form of fly ash. This research aimed to determine the effect of fly ash and water binder ratio (w/b) on the compressive strength of SCC concrete. The variations of fly ash and w/b in this research were 0%, 20, 15, and 20%, with w/b 0.3, 0.35, and 0.4. Cylindrical specimens 150 mm x 300 mm were tested at the age of 28 days to determine the compressive strength of each variation of the mixture. The results showed that the percentage of fly ash and water binder ratio (w/b) could affect the filling and passing ability of SCC fresh and the compressive strength of SCC concrete. That can be shown the compressive strength of SCC at the proportion of fly ash 15% increase of 33.5% and 21.8% compared to SCC without fly ash (0%). However, at 20% fly ash proportion, the compressive strength tends to decrease but is still higher than SCC without fly ash (0%). Keywords: Self compaction concrete, Fly ash, Water binder ratio, Compressive strength ABSTRAK Beton memadat sendiri adalah beton yang dalam keadaan segar mampu mengalir dan mengisi ruangan di dalam cetakan (bekisting) tanpa proses pemadatan. Sehingga dapat mengatasi berbagai permasalahan selama pengecoran elemen bangunan yaitu mengurangi waktu pelaksanaan konstruksi dan besarnya upah tenaga kerja untuk proses pemadatan dan penggetaran, mengurangi kebisingan, meningkatkan kepadatan bagian elemen struktur beton yang tidak dapat dijangkau oleh alat pemadat dan selanjutnya kualitas serta kekuatan struktur beton secara menyeluruh dapat ditingkatkan. Proses produksi semen mengakibatkan peningkatan emisi gas karbondioksida (CO2) sehingga perlu dicarikan bahan arternatif pengganti untuk mengurangi dampak negatif tersebut yaitu dengan memanfaatkan limbah pembakaran batu bara berupa abu terbang (fly ash). Tujuan penelitian ini adalah untuk mengetahui pengaruh fly ash dan water binder ratio (w/b) terhadap kuat tekan beton Self Compaction Concrete (SCC). Variasi prosentase fly ash dan w/b pada peneltian ini adalah 0, 20, 15, dan 20% dengan w/b 0,3, 0,35, dan 0,4. Benda uji silinder 150 mm x 300 mm diuji pada umur 28 hari untuk mengetahui kuat tekan masing-masing variasi campuran. Hasil penelitian menunjukkan bahwa bahwa persentase fly ash dan water binder ratio (w/b) dapat mempengaruhi kemampuan mengalir (filling ability) dan melewati sela-sela tulangan baja (passing ability) beton segar SCC serta kuat tekan beton SCC. Hal ini ditunjukkan dengan meningkatnya kuat tekan SCC pada proporsi fly ash 15 % mengalami peningkatan sebesar 33,5 dan 21,8 % dibandingkan dengan SCC tanpa fly ash (0%). Akan tetapi pada proporsi fly ash 20 % kuat tekan cenderung mengalami penurunan, namun masih lebih tinggi daripada SCC tanpa fly ash (0%). Kata kunci: Beton memadat sendiri, Fly ash, Water binder ratio, Kuat tekan